Songket Palembang dan Bunga Hellebore sebagai Sumber Ide Penciptaan Busana Muslim - Rachmawardani, Rizmaningrum; Suhartini, Ratna (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Hellebore flowers in Indonesian are also called helleborus flowers, a type of flowering plant from the genus Helleborus which is known for its beautiful flowers and often blooms in winter or early spring. The purpose of this study was to determine the results of the application of Palembang songket cloth and Hellebore flowers to Muslim clothing. This study uses a double diamond model research methodology consisting of four stages, namely discovery, definition, development, and application. The main materials used are Palembang songket cloth, duchess cloth, and wool. The garment making process consists of making patterns and adding fabrics that can be manipulated to women’s and men’s clothing. The silhouette of this dress is an A-line silhouette with a loose blouse and accessories. Palembang songket applied to the blazer gives a unique and ethnic impression. The results of this study apply manipulating tucking to the clothing and accessories to give a unique impression so that the appearance looks different.